The Development of Health Insurance and Services in Indonesia - Vita Maylia Ardini; Erlina Puspitaloka Mahadewi (CV. Inara, 2022)
The study focus on the development and review of health insurance in Indonesia that is relatively new for most Indonesians because the term health insurance is not sufficient in the general vocabulary. Social health insurance is insurance that must be followed by all or part of the population (an example employees), to involved and contributions are not a nominal value but a percentage of the salary to be paid, and insurance benefits. Commercial health insurance is insurance sold by other insurance companies or institutions. The development of health insurance in Indonesia is very slow compared to the development of health insurance in several neighboring Asean countries (Associaton of South East Asian Nations). Careful research on the slow development of health insurance in Indonesia is still lacking. However, in theory, several importantfactors can be put forward as factors that influence the slow growth of health insurance in Indonesia. In this case, there are health services which, in the process of health services, there will be variations in the implementation of activities from time to time which will produce varying results. One of the efforts to reduce process variation is standardization. The normalization process includes the elaboration, implementation, follow-up, control, evaluation and revision of norms (Indonesia Government Regulations or PPnumber:102/2000). The development of public health services in Indonesia has succeeded in improving health services more evenly. Advances in science and technology have resulted in more and more educated and informed community groups so that they can choose and demand quality health services especially with health insurances coverage